System CEISA 4.0 dalam Pengelolaan Data Manifest Inward dan Outward pada Kantor Bea Cukai Batam oleh PT. Surya Samudera Indah Batam - Hartanta Capah; Syarifur Ridho; Taruna Taruna (Jurnal Pemimpin Bisnis Inovatif, 2026)
This study discusses the implementation of the CEISA 4.0 System (Customs Excise Information System and Automation) in managing Manifest Inward and Outward data at PT. Surya Samudera Indah under the supervision of the Batam Customs Office. The research is motivated by the need for efficiency and accuracy in customs processes in the era of digitalization. The purpose of this study is to analyze the effectiveness of CEISA 4.0 in supporting customs supervision and services, as well as to identify the challenges encountered during its implementation. The research employs a qualitative descriptive method with a case study approach through observation, interviews, and documentation. The findings show that the implementation of CEISA 4.0 has had a positive impact on the speed and accuracy of manifest data reporting, particularly in document validation and tracking processes. However, several technical barriers such as network disruptions and system errors, as well as non-technical obstacles including limited human resource competence and lack of coordination between the company and customs authorities, were identified. The implications of this research highlight the need for system optimization through technological infrastructure improvement and human resource capacity enhancement to ensure CEISA 4.0 functions more effectively in supporting the smooth flow of national and international logistics.